A History of our American Republic - Linden, Glenn M. (River Forest, Ill. : Laidlaw Bros., 1979)
A textbook of American history beginning with the first settlers who migrated from Eurasia, through the growth and development of a new land, to the 1980's and trends for the future.
Includes bibliographical references and index.
Keywords: United States -- History -- Juvenile literature; United States -- History